Photoinduced absorption and anomalous dichroism in NaCa₂Mn₂V₃O₁₂ garnet as an evidence for the formation of oxygen holes dynamics - Eremenko, V.V.; Gnatchenko, S.L.; Kachur, I.S.; Piryatinskaya, V.G.; Ratner, A.M.; Shapiro, V.V.; Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M. (Физика низких температур, 2005)
It is shown that long-lived photoinduced dichroism in garnets is caused by photoproduced
charges with anisotropic structure, keeping long memory of the pumping light polarization, while
photoinduced absorption is due to all photoproduced charges irrespective of their intrinsic structure.
The charges with anisotropic structure are identified as two-center oxygen holes. The formation
of an oxygen hole is preceded by the excitation of a charge-transfer state with electron partially
transferred to a cation C (V⁵⁺ for NaCa₂Mn₂V₃O₁₂ garnet) from an adjacent oxygen anion.
To turn this excited state into a free hole state requires some time τhole during which the hole axis
can be reoriented resulting in a diminution of dichroism. The time τhole shortens with increasing
ionization potential of the cation C (very high for V⁵⁺). Such a mechanism explains qualitatively a
set of unusual experimental facts, in particular, a very strong dichroism observed just in the
NaCa₂Mn₂V₃O₁₂ garnet, where photoinduced changes of all optical properties disappear after
switching off of the irradiation significantly faster than those in other garnets examined.